Reciprocal exchange orientation to organization, challenge stressor and construal level: Three-way interaction effects on voice behavior - Chen, Long; Unsworth, Kerrie L.; Zhang, Li (Frontiers in Psychology, 2023)
This study extends our understanding of voice behavior by considering a more complete set of reciprocity antecedents. We add employees-organization reciprocal exchange orientation (EO REO) into the antecedent of voice behavior and clarify the boundary condition by examining the joint moderating role of challenge stressors and construal level. The presence of challenge stressors represents a positive work environment, thus employees with a strong EO REO are likely to reciprocate with voice. However, such stressors also lead employees to focus on how to deal with the current challenges, which only aligns with employees who have a low construal level mindset and prefer to think about the details of the job at hand. Hence, we hypothesized that the positive relationship between EO REO and voice behavior in the face of challenge stressors was more likely to exist for employees whose construal level is low rather than high. We collected data from 237 employee-supervisor matched dyads in study 1 and 225 employee-supervisor matched dyads in study 2. These two studies offered support for the three-way interaction hypothesis. Our studies further voice by extending the antecedent and delineating the boundary condition of challenge stressors and construal level.